Social Critique in the Monologue 'Balada Sumarah' by Tentrem Lestari - Harianja, Anjelina Septiana; Harahap, Nurhayati; Triana, Ade (International Journal of Education, Information Technology, and Others, 2023)
This research explores social criticism within Tentrem Lestari's monologue drama, "Baladah Sumarah," employing a qualitative descriptive research approach. Qualitative description, as defined by Moleong (cited in Achmad, 2023: 3), involves the generation of descriptive data in the form of words and images rather than numerical figures. The Qualitative Descriptive Method is employed to analyze the structural and aesthetic values embedded in the monologue. The findings of the study reveal three prominent social criticisms within the monologue, addressing issues related to poverty, criminal activities, and family dynamics. The research concludes that social criticism in literary works serves as a reflection of societal phenomena. In the context of "Baladah Sumarah," the monologue offers social criticism directed at leaders and individuals in positions of power who exhibit tendencies of arrogance toward the lower strata of society. This research contributes to the understanding of social criticism in literature, emphasizing its role as a mirror reflecting prevalent issues within the community. Furthermore, it highlights the effectiveness of qualitative descriptive methods in uncovering and analyzing the intricate layers of social critique present in dramatic literary works.